New records and range extension of the Portuguese dogfish Centroscymnus coelolepis in the south‐western Atlantic Ocean, with comments on its morphology. Issue 3 (25th January 2020) - Mas, Federico; Forselledo, Rodrigo; Domingo, Andrés; Pin, Oscar; Troncoso, Pablo; Errico, Eugenia; Marquez, Alejandro; Tanaka, Sho; Weigmann, Simon
Abstract: The Portuguese dogfish Centroscymnus coelolepis is a wide‐ranging deep‐water shark and a common by‐catch component of the catches of several mid‐ to deep‐water fisheries. In the present study, two new records from the south‐western Atlantic Ocean are reported based on specimens caught by bottom‐longline fishing vessels operating in the Argentinean–Uruguayan Common Fishing Zone. Species identification based on morphology and detailed morphometrics, as well as molecular data are presented for one of the specimens. The distribution of the species over the south‐western Atlantic is discussed on the basis of the available bibliography and a thorough revision of museum collections. The records presented here expand the species' previously acknowledged distribution southwards, from around 21° S to at least 38° S, suggesting it occurs continuously along the shelf break of eastern South America. However, given the limited access to specimens of deep‐water sharks in the region, the abundance and real extent of C. coelolepis distribution in the south‐western Atlantic as well as its interaction with deep‐water fisheries remain to be fully assessed.